Anthropological accounts of leadership: Historical and geographical interpretations from indigenous cultures. (August 2015) - Edwards, Gareth
This paper critiques contemporary leadership theory through a historiography of anthropological accounts. Through this review, the paper highlights a number of nuances in the conceptualisation of leadership from differing indigenous cultures using historical and geographical perspectives. The paper contributes to the leadership literature by taking a longitudinal perspective and providing further evidence of a history of notions akin to distributed leadership. This longitudinal perspective enables the paper to uncover an individualistic focus of leadership studies that appear to override sociologically orientated and distributed perspectives within a particular period of the twentieth century. The review of these studies also seems to point towards a pluralistic paradigm of leadership evidenced early on in the twentieth century.